2015
DOI: 10.1111/1467-8578.12096
|View full text |Cite
|
Sign up to set email alerts
|

Social acceptance and the choosing of favourite classmates: a comparison between students with special educational needs and typically developing students in a context of full inclusion

Abstract: Empirical data on the effects of inclusion regarding the social participation of typically developing students and those with special educational needs are still controversial. While some studies suggest that the more extensive the inclusion, the higher the social position of students with special educational needs, evidence from other studies indicates that the full inclusion of students with special educational needs into ordinary schools is not sufficient, per se, to increase their social participation. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 28 publications
4
29
0
6
Order By: Relevance
“…Thus, there must be other mechanisms influencing the social participation of pupils with ID in inclusive classrooms, for example, the achievement level of these pupils. In fact, Krull et al (2014) and Nepi et al (2015) found a relationship between low academic achievement levels and low social acceptance by peers. Further, on a group level, classroom composition and group norms can also play a crucial role regarding the social participation of individuals in inclusive classrooms (Garrote, 2016;Grütter et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there must be other mechanisms influencing the social participation of pupils with ID in inclusive classrooms, for example, the achievement level of these pupils. In fact, Krull et al (2014) and Nepi et al (2015) found a relationship between low academic achievement levels and low social acceptance by peers. Further, on a group level, classroom composition and group norms can also play a crucial role regarding the social participation of individuals in inclusive classrooms (Garrote, 2016;Grütter et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mere presence of these pupils in general education classrooms does not automatically result in successful social participation. Pupils with SEN are less involved in social interactions with peers, less accepted and more frequently rejected than their typically developing (TD) peers (Avramidis, 2013;Estell et al, 2008;Feldman, Carter, Asmus, & Brock, 2015;Garrote, 2016;Grütter, Meyer, & Glenz, 2015;Huber, 2006;Koster, Pijl, Nakken, & van Houten, 2010;Nepi, Fioravanti, Nannini, & Peru, 2015;Pijl & Frostad, 2010;Rotheram-Fuller, Kasari, Chamberlain, & Locke, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…The most studied dimension of social participation is the social acceptance of pupils with SEN. A majority of the studies show that pupils with SEN included in preschool or primary classrooms are more often rejected and less well accepted by their peers than TD pupils (Avramidis, 2013;Cambra & Silvestre, 2003;Estell et al, 2008;Frederickson, Simmonds, Evans, & Soulsby, 2007;Freeman & Alkin, 2000;Garrote, 2016;Grütter, Meyer, & Glenz, 2015;Hestenes & Carroll, 2000;Huber & Wilbert, 2012;Koster, Pijl, Nakken, & van Houten, 2010;Krull, Wilbert, & Henneman, 2014;de Monchy, Pijl, & Zandberg, 2004;Nadeau & Tessier, 2003;Nowicki, 2003;Nepi, Fioravanti, Nannini, & Peru, 2015;Odom & Diamond, 1998;Pijl & Frostad, 2010;Pijl, Skaalvic, & Skaalvic, 2010;Rotheram-Fuller, Kasari, Chamberlain, & Locke, 2010;Yude, Goodman, McConachie, 1998). This is the case not only during recess but also in the classroom (Cambra & Silvestre, 2003;Frederickson et al, 2007).…”
Section: Social Acceptance Of Pupils With Senmentioning
confidence: 99%
“…The study concluded that we need to do effective educational interventions to social skills of students with or without SEN in schools of general education. Nepi, Fioravanti, Nannini, and Peru (2015) investigated the social position of students with SEN in general classes of primary and high schools in Italy. The purpose of this study was to examine the effects of inclusion in different aspects of social participation, from having positive interactions between students with SEN and those without to the acceptance of the students with SEN and the growth of friendly relationships inside the group of students who grow up together as a whole.…”
Section: Social Skillsmentioning
confidence: 99%